Blended learning approach with web 2.0 tools - Tulaboev, A. (2013)
Online web based learning shifts new platform of web so called Web 2.0 applications are rapidly accelerating market with new challenges and opportunities these implicate as well as in education. This paper investigates technology acceptance of web 2.0 tools in blended learning class setting. The work describes here thoughts in investigation the acceptability and potential use of web 2.0 as an aid to learning. Academic writing skills are subject of experimental class in University. Adoptions of web 2.0 tools are studied in aspect of blended learning setting, where is impact of blended learning approach on combination of online and face-to-face learning activities. The extension of the UTAUT model is used as a research framework to evaluate the acceptability of web 2.0 applications in Teaching and Learning. Â© 2013 IEEE.